Matemática
Dayane2
18

X= 1-[4+(4-2-5) - (-7+3)] Y= 2- [7-(-1-3+6) -8] CALCULE: a) X+Y= b) X-Y= c) X-X=

+1
(2) Respostas
ousada

Resolvendo a expressão de X temos X=-4 e Y=-1 x+y= -4+(-1)= -5 x-y= -4-(-1)= -3 x-x= -4-(-4)= 0

nao

x=1-[4-3+4]                y=2-[7-2-8] x=1-5                         y=2+3                            x=-4                           y=5   x+y                x-y                       x-x  -4+5=1           -4-5=-9                 -4+4=0                    

Adicionar resposta